Calidad de servicio en el Laboratorio Siglo 21 del cantón de Baba, en el periodo 2023. - Gutiérrez Franco, Pensy Dayana (2024)
Customer service in the clinical laboratory is essential for patient satisfaction and efficient operation of the company. Through this case study called quality of service in the 21st century laboratory of the canton of Baba. The quality indicators allow the evaluation of the performance of services and people through this research and the aim is to determine how it affects the way in which services are provided to laboratory patients and to establish if the service provided is of quality and if clients have the desired satisfaction. Service in the term “client in a Laboratory” refers to the care and support of patients from entry to medical care and exit. The present investigation is deductive - inductive and corresponds to a field investigation, it was developed in the laboratory, observations were made and surveys were applied to the patients of the 21st century laboratory in order to identify the deficiencies and weaknesses that exist in the process, provision of services of adequate quality by the company.